The story on older boys - O'Neil, Laura; Copyright Paperback Collection (Library of Congress) (New York : Pocket Books, 1998)
While visiting D.J. at college Stephanie meets a great guy named Eric. The only problem is Eric thinks she's a freshman--how can she tell him she's still in middle school?
"A Minstrel book."
"A Parachute book."
Based on the television series Full house.
Keywords: Teenagers -- Juvenile fiction; College stories; Teenagers -- Fiction; Universities and colleges -- Fiction; Radio and television novels